Formulation and Characterization of Ziprasidone Floating Pellets - Kumar, J Praveen; Harika, S (Journal of Biomedical and Pharmaceutical Research, 2022)
The objective of this study is to design and evaluate Ziprasidone Floating pellets, which prolongs the release rate of the drug while extending the residence time of the drug within the body environment and without causing undeliterious effects to the subject. Ziprasidone and controlled matrix polymer granules were prepared by different granulation techniques in the ratio of 1:1, 1:1.5 and 1:2.Ziprasidone multi unit formulations comprising cellulose polymers were prepared by wet granulation technique, where as the Ziprasidone multi unit formulations comprising lipoidal / fatty polymers were prepared by melt granulation technique. Ziprasidone multi unit formulations with drug and polymer proportion as 1:1, F1 and F2 formulations consisting Cellulose polymers HPMC K4M and HPMC K100 respectively were prepared by wet granulation technique.Keywords: Ziprasidone, wet granulation, Floating pellets, melt granulation and polymer.